Effect of Gradation Variation on Mixture Properties in Stone Mastic Asphalt Mixtures with Carbon Fiber and Hybrid Aggregate - Cahit GÜRER; Ayfer ELMACI KORKMAZ; Burak Enis KORKMAZ; Serhat DÜZAĞAÇ (Medžiagotyra, 2024)
Due to advantages like abrasion resistance, increased operating and service life, high coarse aggregate content and high resistance to deformation, increased fatigue life, and others, stone mastic asphalt (SMA) mixtures have recently become a popular asphalt pavement type in road sections such as highways, tunnels, and bridges. There hasn't been much research on the topic, despite the fact that gradation significantly affects the performance of SMA combinations. In this study, the experimental findings of three distinct gradations of SMA mixtures with hybrid materials (basalt coarse aggregate, limestone fine aggregate) and carbon fiber were compared. As a result, it was concluded that the hybrid aggregate used with carbon fiber, maximum aggregate size, and coarse aggregate % had a positive impact SMA mixtures.